Low genetic diversity of Treponema pallidum ssp. pertenue (TPE) isolated from patients' ulcers in Namatanai District of Papua New Guinea: Local human population is infected by three TPE genotypes - Medappa, Monica; Pospíšilová, Petra; Madruga, Maria Paula M; John, Lucy N; Beiras, Camila G; Grillová, Linda; Oppelt, Jan; Banerjee, Arka; Vall-Mayans, Marti; Mitjà, Oriol; Šmajs, David (PLoS neglected tropical diseases, 2024)
Yaws is an endemic disease caused by Treponema pallidum subsp. pertenue (TPE) that primarily affects children in rural regions of the tropics. The endemic character of yaws infections and the expected exclusive reservoir of TPE in humans opened a new opportunity to start a yaws eradication campaign. We have developed a multi-locus sequence typing (MLST) scheme for TPE isolates combining the previously published (TP0548, TP0488) and new (TP0858) chromosomal loci, and we compared this typing scheme to the two previously published MLST schemes. We applied this scheme to TPE-containing clinical isolates obtained during a mass drug administration study performed in the Namatanai District of Papua New Guinea between June 2018 and December 2019. Of 1081 samples collected, 302 (28.5%) tested positive for TPE DNA, from which 255 (84.4%) were fully typed. The TPE PCR-positivity in swab samples was higher in younger patients, patients with single ulcers, first ulcer episodes, and with ulcer duration less than six months. Non-treponemal serological test positivity correlated better with PCR positivity compared to treponema-specific serological tests. The MLST revealed a low level of genetic diversity among infecting TPE isolates, represented by just three distinct genotypes (JE11, SE22, and TE13). Two previously used typing schemes revealed similar typing resolutions. Two new alleles (one in TP0858 and one in TP0136) were shown to arise by intragenomic recombination/deletion events. Compared to samples genotyped as JE11, the minor genotypes (TE13 and SE22) were more frequently detected in samples from patients with two or more ulcers and patients with higher values of specific TP serological tests. Moreover, the A2058G mutation in the 23S rRNA genes of three JE11 isolates was found, resulting in azithromycin resistance.
Keywords: Treponema; Child; Yaws; Genotype; Treponema pallidum; multilokusová sekvenční typizace; lidé; mutace; Multilocus Sequence Typing; Papua New Guinea; Papua Nová Guinea; Ulcer; vřed; Mutation; Humans; frambézie; dítě; genotyp